Impact of hydration with beverages containing free sugars or xylitol on metabolic and acute kidney injury markers after physical exercise - Wołyniec, Wojciech; Szwarc, Andrzej; Kasprowicz, Katarzyna; Zorena, Katarzyna; Jaskulak, Marta; Renke, Marcin; Naczyk, Marta; Ratkowski, Wojciech (Frontiers in Physiology, 2022)
The proper fluid and carbohydrates intake is essential before and during physical exercise, therefore athletes drink beverages containing a high amount of free sugars. Sweetened soft drinks are also commonly consumed by subjects not doing any sport, and this habit seems to be unhealthy and the cause of metabolic problems. Recently, several sweeteners have been proposed to replace sugars in popular beverages. To examine the impact of free sugars and the popular sweetener xylitol on metabolic profile and markers of kidney function and injury after exercise the present study was conducted with semi-professional football players. All participants were healthy, with a mean age of 21.91 years. Their sports skills were on the level of the 4th-5th division of the league. The subjects took part in four football training sessions. During each session they drank a 7% solution of sugar (sucrose, fructose, glucose) or xylitol. The tolerability of these beverages and well-being during exercise was monitored. Before and after each training session, blood and urine were collected. The markers of kidney function and injury, uric acid, electrolytes, complete blood count, CRP, serum albumin, serum glucose and lipid profile were analyzed. The main finding of this study was that the xylitol beverage is the least tolerated during exercise and 38.89 % of participants experienced diarrhea after training and xylitol intake. Xylitol also led to unfavorable metabolic changes and an enormous increase in uric acid and creatinine levels. A mean increase of 1.8mg/dL in the uric acid level was observed after xylitol intake. Increases in acute kidney injury markers were observed after all experiments, but changes in urine albumin and cystatin C were highest after xylitol. The other three beverages (containing “free sugars” - glucose, fructose and sucrose) had a similar impact on the variables studied, although the glucose solution seems to have some advantages over other beverages. The conclusion is that sweeteners are not a good alternative to sugars, especially during exercise. Pure water without sweeteners should be drunk by those who need to limit their calorie consumption.